SOME OBSERVATIONS ON THE POLLUTION OF THE RIVER SONE BY THE FACTORY EFFLUENTS OF THE ROHTAS INDUSTRIES AT DALMIANAGAR (BIHAR) - Motwani, M P; Banerjea, Santimoy; Karamchandani, S J (Indian Journal of Fisheries, 2015)
With the growing industrial development of India, the problem df disposal of industrial wastes, which hitherto has not gained much importance, will have to be pursued with due consideration to the utilisation of the fishery resources of our national waterways. In other countries considerable attention is devoted to this problem and, by a co-operative eflfort of the Government and the industries, much useful work has been done towards its solution. In India, however, though the seriousness and importance of the problem have been realised {Curr. Sci., 1939; Fowler, 1939; Hora, 1942 and Bhaskaran, 1947) no systematic work appears to have been done except for a few contributions (Hora and Nair, 1944; Bhimachar and David, 1946; Ganapati and Alikunhi, 1950; Seth and Bhaskaran, 1950; Ganapati and Chacko, 1951).